A simple all-solution approach to the synthesis of large ZnO nanorod networks. Issue 8 (26th January 2015) - Resmini, A.; Tredici, I. G.; Cantalini, C.; Giancaterini, L.; De Angelis, F.; Rondanina, E.; Patrini, M.; Bajoni, D.; Anselmi-Tamburini, U.
Abstract : Soft-lithography of Zn-loaded hydrogels and a subsequent hydrothermal growth process yield self-assembling networks of bridging ZnO nanorods (NRs). They are grown on seeding micropillars of ZnO until they touch, forming junctions that provide a preferred electrical path for the operative current of functional devices ( e.g. gas senors). Abstract : ZnO nanorods present great potential for application in optical, sensing and piezoelectric devices; thanks to their nanometric diameter and large surface area. In some of these applications a probing current must flow directly through the nanorods, requiring each nanorod to be directly connected to two electrodes. To attain this architecture a few solutions have been proposed in the past, mostly involving the use of complex and time-consuming procedures, but the large-scale production of such devices represents still a major challenge. We present here a new all-solution approach that allows the fabrication of extensive self-assembled, bi-dimensional networks of ZnO nanorods. Such networks can be easily produced on interdigitated electrodes with no need for any alignment, resulting directly in the formation of very robust devices. The entire process is fast, does not require any complex experimental apparatus and involves only the use of inexpensive and environmentally friendly chemical reagents. We demonstrate the potentiality of such networks in a gas sensing application, where these networks were able to detect NO2 at trace levels, at low temperatures, using UV-visible activation.